PENGARUH KEPEMIMPINAN TERHADAP KINERJA KARYAWAN PADA PERUSAHAAN - Danang Nugroho; Cindy Fitria; Galang Ramadan; Riska Rahayu; Siti Aninditya; Trifany Zahra Nur Annisa (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
ABSTRACT This research explores the influence of leadership on employee performance in companies. A quantitative approach was used to analyze data from employee surveys and performance evaluations in several companies. Findings indicate that effective leadership is positively related to employee performance. Leadership that provides clear direction, adequate support, and facilitates employees' professional development tends to create a productive and satisfying work environment. The practical implications of this research highlight the importance of developing competent and employee-oriented leadership in achieving organizational goals. Further studies could explore additional factors that influence the relationship between leadership and employee performance. The results obtained from this research: leadership has no direct effect on employee performance, work ability also has no direct effect on employee performance, but trust has a direct positive effect on employee performance. Meanwhile, leadership and work ability directly have a positive effect on trust.